Peningkatan Hasil Belajar Volume Bangun Ruang dengan Model Problem Based Learning di Kelas V Sekolah Dasar - Zafira, Nadya Rahma; Masniladevi, Masniladevi (Universitas Negeri Padang, 2024)
This research is motivated by the low results of studying the volume of geometric shapes and the relationship of cubes and cube roots. The purpose of this study was to describe the increase in spatial volume learning outcomes with the Problem Based Learning model in Class V SDN 12 Padang Besi, Padang City. This type of research is Classroom Action Research using qualitative and quantitative approaches. The research procedures are planning, implementing, observing, and reflecting. Data collection techniques in the form of observation, tests and non-tests. The research subjects were teachers as observers, researchers as practitioners, and 25 fifth-grade students. The results showed that the lesson plan for cycle I obtained an average of 86.46% (B), and an increase in cycle II of 93.75% (SB). Implementation of the first cycle of the teacher aspect obtained an average of 86.9% (B), increased in the second cycle by 96.42% (SB). Implementation of the first cycle aspects of students obtained an average of 83.33% (B), increased in the second cycle to 92.85% (SB). The learning outcomes of the first cycle obtained an average of 73.66 (C), increased in the second cycle to 86.01 (B). It was concluded that the use of the Problem-Based Learning model could improve the learning outcomes of geometric volumes and cube and cube roots in Class V SDN 12 Padang Besi